Content aware image restoration improves spatiotemporal resolution in luminescence imaging - Boothe, Tobias; Ivanković, Mario; Grohme, Markus A.; Markus, M. Andrea; Dullin, Christian; Xu, Xingbo; Rink, Jochen C. (Communications biology, 2023)
Luminescent reporters are due to their intrinsically high signal-to-noise ratio a powerful labelling tool for microscopy and macroscopic in vivo imaging in biomedical research. However, luminescence signal detection requires longer exposure times than fluorescence imaging and is consequently less suited for applications requiring high temporal resolution or throughput. Here we demonstrate that content aware image restoration can drastically reduce the exposure time requirements in luminescence imaging, thus overcoming one of the major limitations of the technique.